Edge‐oriented N‐Doped WS2 Nanoparticles on Porous Co3N Nanosheets for Efficient Alkaline Hydrogen Evolution and Nitrogenous Nucleophile Electrooxidation. Issue 40 (1st September 2022) - Liao, Liling; Zhao, Yuling; Zhou, Haiqing; Li, Dongyang; Qi, Ying; Zhang, Yong; Sun, Yang; Zhou, Qian; Yu, Fang
Abstract: Earth‐abundant layered tungsten disulfide (WS2 ) is a well‐known electrocatalyst for acidic hydrogen evolution, but it becomes rather sluggish for alkaline hydrogen or oxygen evolution due to the low‐density edge sites, poor conductivity, and unfavorable water dissociation behavior. Here, an interfacial engineering strategy to construct an efficient bifunctional electrocatalyst by in situ growing N‐doped WS2 nanoparticles on highly conductive cobalt nitride (N‐WS2 /Co3 N) for concurrent hydrogen evolution reaction (HER) and urea oxidation reaction (UOR) is demonstrated. Benefiting from the good conductivity of Co3 N, rich well‐oriented edge sites and water‐dissociation sites at the nanoscale interfaces between N‐WS2 and Co3 N, the resultant N‐WS2 /Co3 N exhibits remarkable HER activity in 1 m potasium hydroxide (KOH) requiring a small overpotential of 67 mV at 10 mA cm −2 with outstanding long‐term durability at 500 mA cm −2, representing the best alkaline hydrogen‐evolving activity among reported WS2 catalysts. In particular, this hybrid catalyst also shows exceptional catalytic activities toward theurea oxidation reaction featured by very low potentials of 1.378 and 1.41 V to deliver 100 and 500 mA cm −2 along with superb large‐current stability in 1 m KOH + 0.5 m urea. Moreover, the assembled two‐electrode cell delivers the industrially practical current density of 500 mA cm −2 at a low cell voltage of 1.72 V with excellent durability in alkaline urea‐containing solutions, outperforming most MoS2 ‐like bifunctional electrocatalysts for overall water splitting reported hitherto. This work provides a promising avenue for the development of high‐performance WS2 ‐based electrocatalysts for alkaline water splitting. Abstract : An in situ interfacial engineering strategy is introduced to construct a highly efficient and stable hybrid catalyst consisting of N‐doped WS2 particles on Co3 N, which presents interesting bifunctional catalytic properties for the hydrogen evolution reaction and nitrogenous nucleophile electrooxidation, demanding only 1.72 V to stably deliver 500 mA cm −2 for electrochemical hydrogen production.